Proceedings of the 2018 Conference on Empirical Methods in Natural Language Processing 2018
DOI: 10.18653/v1/d18-1350
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Capsule Networks with Dynamic Routing for Text Classification

Abstract: In this study, we explore capsule networks with dynamic routing for text classification. We propose three strategies to stabilize the dynamic routing process to alleviate the disturbance of some noise capsules which may contain "background" information or have not been successfully trained. A series of experiments are conducted with capsule networks on six text classification benchmarks. Capsule networks achieve competitive results over the compared baseline methods on 4 out of 6 datasets, which shows the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(93 citation statements)
references
References 22 publications
0
93
0
Order By: Relevance
“…Jaiswal et al reported a capsule-based GAN [70]. Yang et al applied a capsule network to the text domain [71]. Nguyen et al were pioneers in applying capsule networks to the digital media forensics problem [28].…”
Section: Capsule Networkmentioning
confidence: 99%
“…Jaiswal et al reported a capsule-based GAN [70]. Yang et al applied a capsule network to the text domain [71]. Nguyen et al were pioneers in applying capsule networks to the digital media forensics problem [28].…”
Section: Capsule Networkmentioning
confidence: 99%
“…A significant advantage of capsule network is that it performs much better in the transferring single-label to multilabel classification task [13]. Different from traditional deep learning classification models that are based on fully connected network, capsule networks use activity vectors of each capsule in DigitCaps layer to indicate the presence of an instance of each class.…”
Section: Performance Evaluation On Reuters-21578mentioning
confidence: 99%
“…[49], [30], [31] as a kind of supervised representation learning methods, in which groups of neurons are called capsules. Capsule network has been proved effective in learning the intrinsic spatial relationship between features [13], [29], [50]. [13] showed that Capsule networks can help to improve low-data and label transfer learning.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, CapsNet has been applied to several NLP tasks like text classification and relation extraction (Yang et al, 2018b;Gong et al, 2018;Xiao et al, 2018;Wang et al, 2018b). CapsNet is able to adaptively decide the information transferred between layers by using dynamic routing.…”
Section: Definitions and Preliminarymentioning
confidence: 99%